Identification of Reference Genes for Reverse Transcription-Quantitative PCR Analysis of Ginger Under Abiotic Stress and for Postharvest Biology Studies - Li, Gang; Ma, Jiawei; Yin, Junliang; Guo, Fengling; Xi, Keyong; Yang, Peihua; Cai, Xiaodong; Jia, Qie; Li, Lu; Liu, Yiqing; Zhu, Yongxing (Frontiers in Plant Science, 2022)
Gene expression analysis largely improves our understanding of the molecular basis underpinning various plant biological processes. Stable reference genes play a foundational role during the normalization of gene expression levels. However, until now, there have been few reference genes suitable for ginger reverse transcription quantitative PCR (RT-qPCR) research. In this study, 29 candidate reference genes with stable expression patterns among multiple ginger tissues and 13 commonly used reference genes were selected to design RT-qPCR primers. After amplification specificity validation, 32 candidates were filtered and further evaluated by RT-qPCR using samples from different organs subjected to NaCl, drought, heat, waterlogging, and chilling stress. Four strategies, including delta-CT, BestKeeper, geNorm, and NormFinder, were used to rank the stability of reference genes, and the ranks produced by these four strategies were comprehensively evaluated by RefFinder to determine the final rank. Overall, the top three stability reference genes indicated by RefFinder were RBP > ATPase > 40S_S3. Their expression pattern correlation analysis showed that the coefficients among each pair of RBP, ATPase, and 40S_S3 were larger than 0.96, revealing consistent and stable expression patterns under various treatments. Then, the expression of three pathogenesis-related (PR) genes and seven MYB genes in rhizomes during postharvest storage and subjected to pathogen infection were normalized by RBP, ATPase, 40S_S3, RBP & ATPase, ATPase & 40S-S3, and RBP & 40S-S3. The results showed that PR and MYB genes were induced by postharvest deterioration and pathogen infection. The correlation coefficients of RBP/ATPase, RBP/40S_S3, ATPase/40S_S3, RBP & ATPase/ATPase & 40S-S3, RBP & ATPase/RBP & 40S-S3, and ATPase & 40S-S3/RBP & 40S-S3 were 0.99, 0.96, 0.99, 0.99, 1.00, and 1.00, respectively, which confirmed the stability of these three reference genes in postharvest biology studies of ginger. In summary, this study identified appropriate reference genes for RT-qPCR in ginger and facilitated gene expression studies under biotic and abiotic stress conditions.